New technologies in elderly care - Pruszyński, Jacek; Jasik, Agnieszka; Marcinowska-Suchowierska, Ewa; Puzianowska-Kuźnicka, Monika; Zgliczyński, Wojciech Stefan (Wiedza Medyczna, 2022)
The aging society in the European Union (EU) is a long-lasting trend and it is reflected in transformations of the age structure of the European population. These changes lead and will continue to lead to an increasing demand for care and support for elderly persons in the foreseeable future. Bearing this in mind, it is important to define the health and social needs of the elderly subpopulation in order to properly plan and implement actions within the broadly understood senior policy. Advanced age and the related diseases as well as geriatric syndromes are associated with a gradual deterioration of mobility and loss of independence that lead to disability and lower quality of life. According to the Public Opinion Research Centre (CBOS) the second most frequently indicated source of satisfaction of seniors are their ties with the “small homeland”. Responsible senior policy recognizes the fact that the stay of older people in a well-known, friendly environment with which they are emotionally connected, improves their well-being and, if the place of residence is properly adapted to their needs, improves the quality of life. The above rule complements and clarifies the assumptions of the model of community support for seniors taking into account the principles of independence, participation, care, self-fulfilment and dignity. The use of modern supporting technologies such as telecare and telemedicine or mobile phone applications allow for monitoring and support of the elderly, including the chronically ill, using teleinformation tools in their home setting. Since we are still a country with a relatively low level of advancement in terms of economy and digital society, it is necessary to undertake actions aimed at eliminating the existing social divisions through profiling targeted assistance.